Influence of heterogeneity and elevated temperatures on the seismic translational stability of engineered landfills. (1st March 2023) - Annapareddy, V. S. Ramakrishna; Pain, Anindya; Sufian, Adnan; Godas, Srikar; Scheuermann, Alexander
Graphical abstract: Highlights: Proposed a new method to assess the influence of heterogeneity and temperatures. Proposed method yielded 8–22% lower safety factor than existing solutions. The seismic stability was strongly influenced by the frequency of base excitation. Heterogeneity in MSW material showed a strong influence on the seismic stability. Elevated temperatures in landfill resulted in 9–18% reduction in the safety factor. Abstract: This paper proposes a new generalised closed-form solution to estimate the safety factors for translational failure of landfills considering the effects of heterogeneity and temperature variation with the depth of the landfill. The influence of heterogeneity was considered in the form of a shear wave velocity profile, while the influence of temperature was accounted for by considering the temperature-dependent shear strength properties. The proposed method also considered the influence of material damping and the mode change behaviour of the landfill. The safety factor for translational failure of the landfill was estimated using the limit equilibrium-based two-part wedge method. The proposed method was validated by comparing the safety factor obtained from this method with comparable analytical solutions. An extensive parametric study was conducted to demonstrate the influences of the landfill geometry, shear strength properties of municipal solid waste and liner components, parameters of strong ground motion, heterogeneity, and landfill temperature on the calculation of safety factors. The interfacial shear strength properties of liner components played a vital role in the translational stability of landfills compared to the shear strength properties of municipal solid waste. The frequency of base excitation showed a strong influence on landfill stability, while the material damping displayed a nominal effect. For the cases considered in this study, when the frequency of base excitation was close to the fundamental frequency of the landfill, the base acceleration was amplified by 6.7 times which reduced the safety factor by approximately 1.6 times. Heterogeneity and temperature have a significant influence on landfill stability. The increased degree of heterogeneity caused an approximately 27% reduction in the safety factor. For the given set of input parameters, the elevated temperature in the landfill alone decreased the safety factor by a maximum of 18%, while it reduced by approximately 60% under the combined influence of seismic, heterogeneity, and elevated temperature.